Color measurements in annatto (Bixa orellana L.) seeds - Paulo Roberto Nogueira Carvalho; Mariana Aparecida Almeida da Silva; João Victor Silva de Oliveira; Eliane Gomes Fabri; Marta Gomes da Silva (Brazilian Journal of Food Technology, 2024)
Abstract Brazil has emerged as the world's largest producer of annatto seeds (Bixa orellana L.). Fortunately, the increase in national production has been accompanied by an improvement in the quality of this raw material. Annatto is a typical crop of small producers who usually use their empirical knowledge to evaluate the quality of the crop. Thefore, the visual observation of the color of annatto seeds has been considered a quality standard by many producers. To evaluate the scientific evidence, the present study evaluated annatto seeds from 51 accessions of the germplasm bank of the Agronomic Institute (Instituto Agronômico de Campinas - IAC) to determine a possible correlation between the pigment’s contents and the color of annatto seeds as well as the influence of humidity on this correlation. The correlations between the concentrations of pigments, humidity, lipids, and color (L*, a*, b*) were also evaluated. The color was evaluated using a colorimeter with measurements of the CIE L*, a*, b* scale. Only the correlation between the variables moisture and lipids was considered strong through the simple correlation, while the variables bixin content and coordinate a* presented a significant correlation while eliminating the effect of moisture (partial correlation). Thus, a correlation between the red color and the bixin concentration of annatto seeds was observed even though it was a weak correlation. In turn, the color difference (ΔEab) between the samples with higher and lower bixin contents was only 1.44. This difference indicates that large variations in the bixin concentrations may lead to small color changes in the annatto seeds, impairing the use of this criterion for quality control of these seeds.